2013
DOI: 10.1089/neu.2012.2773
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Dysfunction after Primary Blast Injuryin vitro

Abstract: The incidence of blast-induced traumatic brain injury (bTBI) has increased substantially in recent military conflicts. However, the consequences of bTBI on the blood-brain barrier (BBB), a specialized cerebrovascular structure essential for brain homeostasis, remain unknown. In this study, we utilized a shock tube driven by compressed gas to generate operationally relevant, ideal pressure profiles consistent with improvised explosive devices (IEDs). By multiple measures, the barrier function of an in vitro BBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
92
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 86 publications
6
92
0
1
Order By: Relevance
“…This difference could be because bEnd.3 cells are less differentiated than brain-derived microvessel endothelial cells, and which form barriers with lower TEER values than primary brain endothelial cultures used in this report [27]. Nonetheless, our findings in BMECs and in vitro blast studies using bEnd.3 cells [43,44], collectively demonstrate that blast exposure disturbs expression of proteins critical for maintaining BBB integrity.…”
Section: Transverse Riemann Solversmentioning
confidence: 67%
See 4 more Smart Citations
“…This difference could be because bEnd.3 cells are less differentiated than brain-derived microvessel endothelial cells, and which form barriers with lower TEER values than primary brain endothelial cultures used in this report [27]. Nonetheless, our findings in BMECs and in vitro blast studies using bEnd.3 cells [43,44], collectively demonstrate that blast exposure disturbs expression of proteins critical for maintaining BBB integrity.…”
Section: Transverse Riemann Solversmentioning
confidence: 67%
“…Previous work using the continuous cell line, bEnd.3 showed that blast causes a loss of ZO1 and claudin-5 [43,44]. This difference could be because bEnd.3 cells are less differentiated than brain-derived microvessel endothelial cells, and which form barriers with lower TEER values than primary brain endothelial cultures used in this report [27].…”
Section: Transverse Riemann Solversmentioning
confidence: 72%
See 3 more Smart Citations